(3GdJQLeI aj GdWH hGdMceIs - (3GdegOj Hf Ydj, GdUfHQj Gdjefj,J (B815 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPG cJGH eNJUQ , hVYJg ai Yde GdWH , hgPHJ CZQGVg hbQHJ CYQGVg , hLYdJg LGeYkG s
(3BNQgG (B:s
(3eHJhQ GdBNQ , jfJgi CKfGA GdcdGe Ydi YdGL GdTYQI GdTYjQI , HbhdI hcPdc Gdebd GdCRQb HdYGH GdUGFe EPG Wdi HgG GdTYjQI MddgG hCVeQgG s
(3eQJH Ydi NeS CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B90 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs